Public private partnerships : success and failure factors for in-transition countries - Urio, Paolo (University Press of America, 2010)
Public-Private Partnerships aims to discover the conditions under which public private partnerships may provide a viable alternative to the provision of public services and infrastructures by the state, while achieving efficient, sustainable, peaceful, and equitable development in four transition countries: China, Poland, Russia, and Ukraine. These countries have experienced command economy under communist rule for at least thirty years. They have only recently introduced market mechanisms. In spiteof a huge literature in favor of public private partnerships in the west, scientific empirical e.